Analysis of the rape culture rentability for nonirrigated and unirrigated production systems - Ionut Laurentiu Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
This paper proposes the analysis of economic indicators referring to the feasibility and efficiency of rapeseed cultivation in two different irrigated and non-irrigated systems, in order to determine the eventual higher profitability of the increase in production. The question of the research is the following: is it more efficient to ensure that the rapeseed is irrigated in order to obtain higher yields? In order to answer this question, we will use data taken from ADER 13.1.2, coordinated by the Research Institute for the Economy of Agriculture and Rural Development, referring to the technological data and the budget for the income and expenditure of the rapeseed. With the help of these, certain technical and economic indicators will be determined by means of which the final conclusion of this study can be established.
Keywords: Q12; Q15; 330; rapeseed culture; profitability; irrigation; non-irrigation